2016
DOI: 10.3389/fimmu.2016.00330
|View full text |Cite
|
Sign up to set email alerts
|

Hematopoietic Stem Cell Regulation by Type I and II Interferons in the Pathogenesis of Acquired Aplastic Anemia

Abstract: Aplastic anemia (AA) occurs when the bone marrow fails to support production of all three lineages of blood cells, which are necessary for tissue oxygenation, infection control, and hemostasis. The etiology of acquired AA is elusive in the vast majority of cases but involves exhaustion of hematopoietic stem cells (HSC), which are usually present in the bone marrow in a dormant state, and are responsible for lifelong production of all cells within the hematopoietic system. This destruction is immune mediated an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
55
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(57 citation statements)
references
References 182 publications
(248 reference statements)
1
55
0
1
Order By: Relevance
“…IFNγ has been implicated in the pathophysiology of BMF syndromes (12,13). A previous study has shown that IFNγ augments the expression of Fas and other pro-apoptotic genes and causes destruction of hematopoietic cells via Fas-mediated apoptosis (14).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…IFNγ has been implicated in the pathophysiology of BMF syndromes (12,13). A previous study has shown that IFNγ augments the expression of Fas and other pro-apoptotic genes and causes destruction of hematopoietic cells via Fas-mediated apoptosis (14).…”
Section: Discussionmentioning
confidence: 99%
“…A pro-inflammatory milieu and sensitivity of hematopoietic stem/progenitor cells (HSPC) to inflammatory cytokines such as TNF-α, IL-6 and IFNγ have been shown to suppress normal hematopoiesis (5,11). In particular, there is significant evidence for IFNγ playing a key role in marrow failure syndromes (12)(13)(14). However, there are different theories, which are sometimes conflicting, regarding the mechanism by which IFNγ promotes BMF.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Under normal circumstances, humans have approximately 11,000 haematopoietic stem cells (HSCs), up to 30% of which are estimated to actively contribute to haematopoiesis, with steady-state haematopoiesis primarily maintained by long-lived multipotent progenitors and short-term (ST) HSCs (Abkowitz, et al 2002, Busch, et al 2015, Catlin, et al 2011). In AA, immune-mediated depletion of haematopoiesis-maintaining cells, probably multipotent progenitors and ST-HSCs, leads to aplasia and cytokine-driven marrow suppression (Busch, et al 2015, Catlin, et al 2011, Smith, et al 2016). It is not known whether long-term HSCs are also directly targeted by immune-mediated destruction, or whether HSC loss occurs through attrition and differentiation.…”
Section: Forces That Drive Clonal Haematopoiesis In Aplastic Anaemiamentioning
confidence: 99%
“…Aplastic anemia (AA) is a rare and life‐threatening disease characterized by heterogeneous bone marrow (BM) failure and peripheral pancytopenia . Since BM fails to support the production of all three lineages of blood cells, AA patients are always accompanied with pancytopenia, anemia, leukopenia, and thrombocytopenia . Hematopoietic stem cell (HSC) transplantation and anti‐thymocyte globulin combined with cyclosporine A and glucocorticoids are the main therapeutic strategies in AA, while the therapeutic efficacy is still limited …”
Section: Introductionmentioning
confidence: 99%